Sexual Assault during the Time of Gulf War I: A Cross-sectional Survey of US Service Men who Later Applied for Department of Veterans Affairs PTSD Disability Benefits - Murdoch, Maureen (Mil Med, 2014)
OBJECTIVES: To estimate the cumulative incidence of sexual assault during the time of Gulf War I among male Gulf War I Veterans who later applied for Department of Veterans Affairs (VA) PTSD disability benefits and to identify potential risk and protective factors for sexual assault within the population. METHOD: Mailed, national, cross-sectional survey supplemented with VA administrative and clinical data. RESULTS: Of 2,415 Veterans sampled, 1,700 (70%) responded. After adjusting for non-ignorable missing data, the cumulative incidence of sexual assault during Gulf War I in this population ranged from 18% [95% confidence intervals (CI): 5.0%-51.9%] to 21% (95% CI: 20.0-22.0). Deployment was not associated with sexual assault [Odds Ratio (OR), 0.96; 95% CI: 0.75-1.23], but combat exposure was (OR, 1.80; 95% CI: 1.52-2.10). Other correlates of sexual assault within the population included working in a unit with greater tolerance of sexual harassment (OR, 1.80; 95% CI: 1.52-2.10) and being exposed to more sexual identity challenges (OR, 1.76; 95% CI: 1.55-2.00). CONCLUSIONS: The 9-month cumulative incidence of sexual assault in this particular population exceeded the lifetime cumulative incidence of sexual assault in US civilian women. While Persian Gulf deployment was not associated with sexual assault in this population, combat exposure was.